2018
DOI: 10.1590/1807-1929/agriambi.v22n4p255-260
|View full text |Cite
|
Sign up to set email alerts
|

Hydropriming as inducer of salinity tolerance in sunflower seeds

Abstract: A B S T R A C TSunflower is a species with multiple potentialities and its yield can be affected by the presence of soluble salts in the soil, which is common in arid, semi-arid and irrigated regions. The objective of this study was to evaluate the effect of hydropriming as inducer of salinity tolerance in seeds and seedlings of sunflower, hybrid MG305CP. The germination tests were set with four replicates of 50 seeds per treatment, maintained in germinator at 30 ºC for ten days. To simulate salinity, sodium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…This is because the seed priming can develop different defense mechanisms in seeds against salinity stress (IBRAHIM, 2016). Efficiency of seed priming with water or KNO 3 in improving root dry matter accumulation under stressful conditions was also reported in watermelon in eggplant (NASCIMENTO & LIMA, 2008), tomato (EBRAHIMI et al, 2014, and sunflower (MATIAS et al, 2018).…”
Section: Effect Of Seed Priming and Salt Stress On Initial Seedling Gmentioning
confidence: 59%
See 4 more Smart Citations
“…This is because the seed priming can develop different defense mechanisms in seeds against salinity stress (IBRAHIM, 2016). Efficiency of seed priming with water or KNO 3 in improving root dry matter accumulation under stressful conditions was also reported in watermelon in eggplant (NASCIMENTO & LIMA, 2008), tomato (EBRAHIMI et al, 2014, and sunflower (MATIAS et al, 2018).…”
Section: Effect Of Seed Priming and Salt Stress On Initial Seedling Gmentioning
confidence: 59%
“…BATISTA et al 2015reported that both hydropriming and osmopriming improved germination and seed germination rate index of pepper seeds compared to unprimed seeds. Matias et al (2018) indicated that hydropriming improved tolerance of sunflower plants under saline environments. According to KUBALA et al (2005), the priming can improve germination rate through metabolic activation involving the synthesis of proteins, nucleic acids, and enzymes, and increasing water uptake, respiratory activity, and reserve mobilization.…”
Section: Source Of Variationmentioning
confidence: 99%
See 3 more Smart Citations